Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi Jambi, Kalimantan Barat, Kalimantan Tengah, Sulawesi Tenggara Tahun 2023/2024 - Achmad Raihan; Mifdzal Azriel; Muhammad Lutfi Syabriyan; Muhammad Rofi Baihaqi (CV. Multi Kreasi Media, 2024)
This study analyzed the age distribution of principals and teachers in Jambi, West Kalimantan, Central Kalimantan, and Southeast Sulawesi in the 2023/2024 school year to understand the need for renewal of the teaching force. Data were obtained from the Ministry of Education, Culture, Research, and Technology, and analyzed using histograms, frequency polygons, and ogives. The results show an age imbalance in the teaching force, especially in remote areas, which risks a shortage of teachers in the near future. Recommendations include recruitment of young teachers, continuous training and strategic planning to ensure the continuity and quality of education.